Hai nghìn linh tám 2008 coding workbook for the physician's office - Covell, Alice (Thomson Delmar Learning, 2005)
This workbook contains coding exercises that reference each section of the CPT and ICD-9-CM coding manuals. Exercises requiring HCPCS Level II codes are also provided. Condition and procedure statements in the exercises reflect the current annual editions of the coding manuals. By completing the exercises, you will expand your medical vocabulary, improve coding skills for the physician's office, and learn to code only what the documentation supports. Also included are the Center for Medicare and Medicaid Services (CMS) guidelines for diagnosis coding and reporting by physicians. Learners need current CPT, ICD-9-CM, and HCPCS coding manuals to complete the exercises